THE USE OF THE KANBAN SYSTEM: A COMPARISON WITH THE DEVELOPMENT OF THE THEORY OF RESTRICTIONS (T.O.C) IN A COMPANY OF AUTOMOTIVE RUBBER DEVICES - Oliveira, Rafael de Abreu; Gasparotto, Angelita Moutin Segoria (Revista Interface Tecnológica, 2020)
Considering the wide range of technologies and the adaptation of automotive companies to create new launches of vehicles, parts and accessories, always looking for guidelines for cost reduction and longer production times, the Kanban method, originating in Japan, provides great assistance for automakers and service providers. Considering that the method is simple and inexpensive, it is worth mentioning its use and how the implementation in which managers can benefit from this type of process in this automotive industrial segment. The viability of the method is evaluated not only by the tactical level, but the operational level also need to adapt to this new growing reality, seeking improvements in their manufacturing environment. However, this article brings an attempt to create a comparison of the development of the Kanban system in its implementation and monitoring, with the application of the Theory of Constraints methodology and its performance indicators in the industry. Due to its flexibility, Kanban and T.O.C (Theory of Restricions) has become more adjustable according to the needs of managers and directors who seek greater production at low production cost, in line with the principles of Theory of Restrictions. From this point on, it is worth emphasizing the mutual importance of these two methods together with production, a lean manufacturing, without waste and seeking continuous improvement in its processes.
Keywords: Theory of The Restrictions; Process; Kanban System